ОСОБЛИВОСТІ ПЕРЕКЛАДУ МЕТАФОРИ ТА МЕТАФОРИЧНИХ ВИРАЗІВ В АНГЛІЙСЬКІЙ ТА УКРАЇНСЬКІЙ МОВАХ (НА МАТЕРІАЛІ НАУКОВО-ТЕХНІЧНИХ ТЕКСТІВ) (Zaporizhzhia Historical Review, 2021)
The article deals with metaphor and metaphorical means translation peculiarities. Metaphor is an important component of scientific-technical texts, which reflects dynamics of lively language functioning in scientific-technical communicational sphere. Interlingual equivalents of metaphorical means are high on the agenda currently due to the necessity of comprehensive scientific-technical language study on the modern stage of scientific-technical progress. Thus on the basis of comparative analysis of SL and TL texts the research determines basic lexical-stylistic transformations of metaphorical means translation in scientific-technical texts.